Stigma and discrimination against people living with HIV by health care providers in Egypt - Mirette M. Aziz; Shaimaa S. Abdelrheem; Heba M. Mohammed (BMC, 2023)
Abstract Objective HIV/AIDS has been recently increasingly observed in developing countries including Egypt. This study aimed to explore stigma and discrimination attitudes of health care providers (HCPs) in Egypt, as elimination of stigma in healthcare settings is a priority to improve case detection and management. Methods A Google form questionnaire using the validated Arabic version of Health Care Provider HIV/AIDS Stigma Scale (HPASS) was sent to physicians and nurses of Ministry of health (MOH) hospitals and University hospitals in 10 randomly selected Governorates in Egypt. Data was collected from July to August, 2022 from 1577 physicians and 787 nurses. Bivariate and multivariable linear regression analyses were used to identify the predictors of the stigmatizing attitude of HCPs towards People living with HIV (PLHIV). Results The majority of HCPs had worries about contracting HIV infection from their patients (75.8% of physicians and 77% of nurses). They believed that protective measures are not good enough to protect them from getting infected (73.9% of physicians and 74.7% of nurses). About half of the participants had worries about the safety of performing blood investigations to PLHIV (54% of physicians and 59.9% of nurses). Less than half of HCPs believed they have the right to refuse providing care to patients to protect themselves (44.6% of physicians and 50.1% of nurses). Only 10.5% of physicians and 11.9% of nurses have previously refused to provide health care to PLHIV. There was a significantly higher mean score of prejudice and stereotype among nurses compared to physicians (prejudice; 27.34 ± 7.88 vs 26.17 ± 7.5, stereotype; 18.54 ± 4.61 vs 16.43 ± 5.21, for nurses and physicians, respectively). Less years of physicians' experience (B = -0.10, p < 0.01) and rural residence (B = 1.48, p < 0.05) were significantly associated with higher prejudice score while having lower qualification (B = -1.47, p < 0.001) was significantly associated with higher stereotype score. Conclusion Standards of practice should be developed to adjust the services and prepare HCPs to provide medical care free from stigma and discrimination against PLHIV. Improving knowledge of HCPs regarding the methods of transmission of HIV, the use of infection control measures and the emotional factors shaping lives of PLHIV should be targeted through updated training programs. More concern should be directed to young providers in the training programs.